Struck - Bosworth, Jennifer (Farrar Straus Giroux, 2012)
After a major earthquake devastates Los Angeles, seventeen-year-old Mia wants only to take care of her younger brother and traumatized mother, but two fanatical doomsday cults vie for her powers, drawn from the multiple lightning strikes she has experienced.